A Large Eddy Simulation Study of Bluff Body Flame Dynamics Approaching Blow‐Off. Issue 7 (3rd July 2017) - Hodzic, E.; Alenius, E.; Duwig, C.; Szasz, R. S.; Fuchs, L.
ABSTRACT: The mechanisms leading to blowoff were investigated numerically by analyzing bluff body stabilized flame at two conditions: a condition far from blowoff to a condition just prior to blowoff. Large eddy simulations have been used to capture the time dependent, three-dimensional evolution of the field. The results were first validated to available experimental data, showing very good agreement for the flow and overall good agreement for the flame. Changes in the large-scale structures are investigated by means of proper orthogonal decomposition and the wavelet method, elucidating the underlying dynamics of the complex flow-flame interaction of a flame approaching blowoff. Our results reveal that, when the flame approaches blowoff conditions, significant changes are found in the large-scale structures responsible for entrainment of species into the recirculation zone located downstream of the bluff body. Possible causes of this shift in large-scale structures are also discussed, which may be useful for extending the blowoff limits of bluff body stabilized burners.